Perfil epidemiológico de micoses em pacientes atendidos em um laboratório privado de João Pessoa-PB e atividade anti-Trichophyton rubrum de citronelal, (R)-(+)- citronelal e (S)-(-)- citronelal - Andrade Júnior, Francisco Patricio de (2024)
The present study aimed to elucidate the epidemiological profile of those affected by mycoses diagnosed in a clinical analysis laboratory in João Pessoa-PB and to investigate the antifungal activity of citronellal (CIT), (R)-(+)- citronellal (R-CIT) and (S)-(-)-citronellal (S-CIT) against clinical isolates of Trichophyton rubrum. This is an epidemiological, descriptive, retrospective and analytical study, carried out in a laboratory in João Pessoa-PB, between 2015 and 2019, analyzing the variables: sex, ethnicity, age group, fungal species and genera and site of injury. Furthermore, it was also presented as experimental research, in which the antifungal potential of CIT, R-CIT and S-CIT was investigated, based on the Minimum Inhibitory Concentration (MIC), Minimum Fungicide Concentration (CFM), Association by using the checkerboard method, and tests with cholesterol, ergosterol and sorbitol, to elucidate possible mechanisms of action. Between the years 2015 and 2019, 1,204 suspected mycoses were analyzed, however, only 323 cases were recorded, with 2015 being the most prevalent (28.1%), the clinical and epidemiological profile was mainly composed of individuals female (71.2%), aged 18 to 59 (57.6%), white (54.2%), with nail (46.7%) and skin (32.8%) injuries, with C.albicans (25.7%) being the main pathogen identified. The MIC values of CIT, R-CIT and S-CIT ranged from 4 to 512 µg/mL. The CFM for CIT ranged from 4 to 512 µg/mL, while R-CIT and SCIT ranged from 4 to 1024 µg/mL. Furthermore, all natural products were predominantly fungicidal. When associating CIT and its isomers with the drug fluconazole, indifference and pharmacological antagonism were evident. Regarding the mechanism of action, all natural products are related to fungal ergosterol. Furthermore, the three terpenes tested show interactions with exogenous cholesterol. The data from the present study can allow us to understand the most recurrent mycoses in João Pessoa-PB, which can allow the creation of preventive and curative measures for the most susceptible population. Furthermore, CIT, R-CIT and S-CIT appear capable of becoming products for the treatment of dermatophytosis in the future.